Long-Term Outcome After Operative Management of Talus Fractures. (December 2018) - Vints, Wouter; Matricali, Giovanni; Geusens, Eric; Nijs, Stefaan; Hoekstra, Harm
Background: Controversies remain regarding the preferred treatment strategy for talus fractures. The primary goal of this study was to evaluate the long-term outcome after operative management of talus fractures. Secondarily, we identified those factors that affected the outcome and defined strategies to improve the outcome. Methods: This is a retrospective outcome study of 84 patients with an average follow-up time of 9.1 years. We assessed the functional results, return to daily activities, and general health status using the Foot Function Index-5pt, a numeric rating scale for pain, and the Short Form-36 Health Survey. Furthermore, we conducted a correlation analysis between the outcomes and 14 demographic, clinical, and radiologic variables. Results: We found moderate mean Foot Function Index pain and disability scores of 30.2 and 28.7, respectively. The mean numeric rating scale score was 3.2. Of all responders, 41% (27/66) did not return to their daily activities. We reported low physical, but good mental, Short Form-36 component summary scores of 42.7 and 48.3, respectively. We recorded a complication rate of 56%. Osteoarthritis, articular incongruence and talus body fractures correlated significantly with a poorer functional outcome. Delayed surgery after trauma was associated with better outcome measures. Conclusions: Talus fractures have a major long-term impact on ankle and hindfoot function and on physical health. Success of operative treatment depends on the occurrence of osteoarthritis postoperatively, type of fracture, and quality of fracture reduction. Because only the latter is modifiable, efforts should be made to restore articular congruence in order to improve the outcome. Therefore, we recommend reviewing the quality of the reduction postoperatively on CT. Furthermore, talus fractures should not be considered operative emergencies, but rather treated after recovery of the soft-tissues. Level of Evidence: Level III, comparative study.